2015
DOI: 10.1038/srep08877
|View full text |Cite
|
Sign up to set email alerts
|

Sink property of metallic glass free surfaces

Abstract: When heated to a temperature close to glass transition temperature, metallic glasses (MGs) begin to crystallize. Under deformation or particle irradiation, crystallization occurs at even lower temperatures. Hence, phase instability represents an application limit for MGs. Here, we report that MG membranes of a few nanometers thickness exhibit properties different from their bulk MG counterparts. The study uses in situ transmission electron microscopy with concurrent heavy ion irradiation and annealing to obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Post-irradiation bright-field TEM images and diffraction patterns show that the MG shell remains amorphous (Figure E,F). Irradiation-induced nanocrystal formation has been observed in various bulk MGs. Enhanced atomic mobility due to the increase in free volume during irradiation is thought to drive crystallization. , For thin, <15 nm, MG films, it has previously been observed that the excess free volume formed by irradiation is rapidly annihilated at the free surface, which prevents changes in atomic mobility and nanocrystal formation . This may also occur in the Au@NiB nanocubes inhibiting crystallization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-irradiation bright-field TEM images and diffraction patterns show that the MG shell remains amorphous (Figure E,F). Irradiation-induced nanocrystal formation has been observed in various bulk MGs. Enhanced atomic mobility due to the increase in free volume during irradiation is thought to drive crystallization. , For thin, <15 nm, MG films, it has previously been observed that the excess free volume formed by irradiation is rapidly annihilated at the free surface, which prevents changes in atomic mobility and nanocrystal formation . This may also occur in the Au@NiB nanocubes inhibiting crystallization.…”
Section: Resultsmentioning
confidence: 99%
“…41,42 For thin, <15 nm, MG films, it has previously been observed that the excess free volume formed by irradiation is rapidly annihilated at the free surface, which prevents changes in atomic mobility and nanocrystal formation. 45 This may also occur in the Au@NiB nanocubes inhibiting crystallization.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…), as described above. In addition, the change of the contrast in the TEM images could be caused by the rearrangement of the lattice defects by thermal activation 29,30 . In actuality, the polygonal-shaped contrast in the α-phase NaYF 4 :Yb,Er UCNPs is not explained by the pure electron-beam effect.…”
Section: Resultsmentioning
confidence: 99%
“…[79,80] The latter are rather stiff, but even proteins being natively soft in a free state become much more rigid under deformation in confinement. [81,82] In any case, the organic/inorganic interactions in biocomposites will lead to much larger deformation of the more compliant organic substance than that of a mineral.…”
Section: Physical Origin Of Anisotropic Lattice Distortionsmentioning
confidence: 99%